2007
DOI: 10.1096/fj.06-6927com
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds from feces and their potential for diagnosis of gastrointestinal disease

Abstract: Little is known about the volatile organic compounds (VOCs) in feces and their potential health consequences. Patients and healthcare professionals have observed that feces often smell abnormal during gastrointestinal disease. The aim of this work was to define the volatiles emitted from the feces of healthy donors and patients with gastrointestinal disease. Our hypotheses were that i) VOCs would be shared in health; ii) VOCs would be constant in individuals; and iii) specific changes in VOCs would occur in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
415
2
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(442 citation statements)
references
References 42 publications
12
415
2
13
Order By: Relevance
“…Indeed, all metabolites enriched in the mountain gorilla metabolome, and in lowland gorillas during the low ripe fruit season (that is, butanoic, propanoic, benzoic and fumaric acids as well as galactopyranosides) can be derived from microbial metabolism on plant cell walls (Pena et al, 2004;Garner et al, 2007). Moreover, we present evidence that the abundance of these metabolites and other components of the lignified portion of plant cell walls, such as caffeic, azelaic, quinic and adipic acid (Moco et al, 2012;Chung, 1997), co-vary along with the abundance of taxa related to unclassified Bacteroidales and Porphyromonadaceae, which could potentially be playing a fibrolytic role in the gut microbiome of mountain gorillas and the lowland species during the low ripe fruit season.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all metabolites enriched in the mountain gorilla metabolome, and in lowland gorillas during the low ripe fruit season (that is, butanoic, propanoic, benzoic and fumaric acids as well as galactopyranosides) can be derived from microbial metabolism on plant cell walls (Pena et al, 2004;Garner et al, 2007). Moreover, we present evidence that the abundance of these metabolites and other components of the lignified portion of plant cell walls, such as caffeic, azelaic, quinic and adipic acid (Moco et al, 2012;Chung, 1997), co-vary along with the abundance of taxa related to unclassified Bacteroidales and Porphyromonadaceae, which could potentially be playing a fibrolytic role in the gut microbiome of mountain gorillas and the lowland species during the low ripe fruit season.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on application of fecal VOC analysis in infectious disease have focused on Clostridium difficile [19][20][21][22][23]. Other studies include detection of Campylobacter jejuni, cholera, giardiasis and rotavirus [21,[23][24][25][26].…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…In addition, three other studies demonstrated that, by means of GC-MS, C. difficile positive fecal samples could be distinguished from controls based on their VOC profiles. Specific VOCs, sensitivity and specificity are listed in Table 2 [19,21,23].…”
Section: Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile organic compounds are gaseous carbon-based chemicals derived from biochemical metabolism in the body, and in the bowel they are mainly produced by the intestinal microbiota and excreted by the feces [82] . Electronic nose has already been proposed as a potential noninvasive diagnostic biomarker test for lung cancer, breast cancer and malignant melanoma [83,84] , and recently [85] , it was shown to discriminate healthy subjects from patients with CRC (sensitivity and specificity: 85% and 87%, respectively) and patients with ADA (sensitivity and specificity: 62% and 86%, respectively).…”
Section: Electronic Nosementioning
confidence: 99%